Efficiency in the public management of health for the municipalities of Ceará - Nunes, Erivelton de Souza (2019)
Although health is of paramount importance and contributes in a direct manner to other social priorities, such as well-being, education, productivity and economic development, the State of Ceará has been getting along with different problems related to the infrastructure in this sector. Because the public funds made available for the fulfillment of the populational demands are limited, it is relevant that the public sector seeks more efficient ways of managing them. Therefore, this study is aimed to measure the technical and scale efficiency scores of the Municipal Development FIRJAN Index (IFDM) in the area of health for the municipalities of Ceará and to gather such efficiency levels according to mesoregion, per capita GDP and in population terms. In order to fulfill these objectives, it was used the Data Envelopment Analysis model for 162 municipalities of Ceará, using secondary data for the year 2013. The results indicate that the majority of the municipalities of Ceará exhibited a problem in relation to the scale of production, caused by the presence of decreasing returns to scale. It has also been observed that not necessarily the municipalities located in more developed regions, with larger per capita GDP and population sizes are managing their resources in the most efficient way possible.